2002
DOI: 10.1021/bi011550s
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the INK4-CDK4/6-Rb Pathway:  Counter Action of Gankyrin against INK4 Proteins Regulates the CDK4-Mediated Phosphorylation of Rb

Abstract: The newly discovered oncogenic protein gankyrin, which contains six ankyrin repeats, has been reported to be involved in the phosphorylation and degradation of the retinoblastoma gene product, Rb. Using in vitro systems, we have identified a peptide fragment of gankyrin, 176LHLACDEERN185, which is responsible for binding of gankyrin to Rb. We further demonstrated a different mechanism for gankyrin to facilitate the phosphorylation of Rb, by binding with cyclin-dependent kinase 4 (CDK4). This binding does not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(136 citation statements)
references
References 21 publications
6
130
0
Order By: Relevance
“…For example, in addition to INK4 proteins, two AR proteins, gankyrin (seven ARs) and IκBR (six ARs), have been reported to physically contact CDK4 and influence the kinase activity in vivo and in vitro (59)(60)(61)(62)(63) (Figure 5a). Gankyrin is an oncoprotein with multiple functions (see below) and is able to compete with p16 and p18 for CDK4 binding, thus counteracting the inhibitory activities of p16 and p18 (59). IκBR usually acts as a specific inhibitor of NF-κB (a transcription factor controlling vital genes involved in immune response, cell growth and differentiation, cell adhesion, and apoptosis) (28,29), but it has the potency to bind to and inhibit CDK4 (63).…”
Section: Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in addition to INK4 proteins, two AR proteins, gankyrin (seven ARs) and IκBR (six ARs), have been reported to physically contact CDK4 and influence the kinase activity in vivo and in vitro (59)(60)(61)(62)(63) (Figure 5a). Gankyrin is an oncoprotein with multiple functions (see below) and is able to compete with p16 and p18 for CDK4 binding, thus counteracting the inhibitory activities of p16 and p18 (59). IκBR usually acts as a specific inhibitor of NF-κB (a transcription factor controlling vital genes involved in immune response, cell growth and differentiation, cell adhesion, and apoptosis) (28,29), but it has the potency to bind to and inhibit CDK4 (63).…”
Section: Specificitymentioning
confidence: 99%
“…Binding of gankyrin to Rb, S6 ATPase of the 26S proteasome, and HDM2 facilitates the ubiquitin-mediated degradation of Rb, HDM2, and other proteins (65,(67)(68)(69), while binding of gankyrin to MAGE-A4 quenches the oncogenic activity of gankyrin through unknown mechanisms (66). Protein fragmentation studies have demonstrated that the first four ARs of gankyrin are involved in interacting with CDK4 and the last two ARs are responsible for binding to Rb (59). The multiple specificities of ARs are potentially physiologically significant, through which distinct pathways are cross-linked or coordinated (Figure 5d).…”
Section: Specificitymentioning
confidence: 99%
“…Under our in vitro assay conditions, p34 SEI-1 acts as both an activator and inhibitor of CDK4, which distinguishes p34 SEI-1 from other CDK4-binding proteins. INK4 (5)(6)(7)(8)(9)(10)(11) and KIP proteins (12)(13)(14) only inhibit CDK4; gankyrin functions as a competitor to antagonize INK4 proteins (17), while Tax is competent in activating CDK4 (15,16), quenching p16 (32,33), and affecting cyclin Ds (34). It is important to point out that most of these studies were performed by in vitro or cell-based studies, and their biological relevance remains to be established.…”
Section: Dissecting the Structural Elements For The Different Functiomentioning
confidence: 99%
“…While binding of D cyclins is required for the full kinase activity (4), INK4 (including p16, p15, p18, and p19) (6)(7)(8)(9)(10)(11) and KIP (including p21, p27, and p57) proteins (5,(12)(13)(14) are inhibitors of CDK4 and 6. Moreover, the oncoprotein Tax from human T-cell leukemia virus 1 (HTLV-1) stimulates the CDK4 activity in infected cells through physical association (15,16), and the oncoprotein gankyrin affects CDK4 by counteracting against the inhibition of p16 and p18 (17). The intricate regulation of CDK4 and 6 activitied by these and possibly many other proteins is crucial for cell cycling and tumorigenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation